The SIC protocol: A seven-step strategy to minimize complications potentially related to the insertion of centrally inserted central catheters. Issue 2 (March 2023) - Brescia, Fabrizio; Pittiruti, Mauro; Ostroff, Matthew; Spencer, Timothy R; Dawson, Robert B
Insertion of central venous catheters in the cervico-thoracic area is potentially associated with the risk of immediate/early untoward events, some of them negligible (repeated punctures), some relevant (accidental arterial puncture), and some severe (pneumothorax). Furthermore, different strategies adopted during insertion may reduce or increase the incidence of late catheter-related complications (infection, venous thrombosis, dislodgment). This paper describes a standardized protocol (S.I.C.: Safe Insertion of Centrally Inserted Central Catheters) for the systematic application of seven basic beneficial strategies to be adopted during insertion of central venous catheters in the cervico-thoracic region, aiming to minimize immediate, early, or late insertion-related complications. These strategies include: preprocedural evaluation, appropriate aseptic technique, ultrasound guided insertion, intra-procedural assessment of the tip position, adequate protection of the exit site, proper securement of the catheter, and adequate coverage of the exit site.